The Role of Prestroke Glycemic Control on Severity and Outcome of Acute Ischemic Stroke - Clara Hjalmarsson; Karin Manhem; Lena Bokemark; Björn Andersson (Stroke Research and Treatment)
Background/Aim. Relatively few studies have investigated the association of prestroke glycemic control and clinical outcome in acute ischemic stroke (IS) patients, regardless of presence of diabetes mellitus (DM). The aim of this study was to investigate the importance of prestroke glycemic control on survival, stroke severity, and functional outcome of patients with acute IS. Methods. We performed a retrospective survival analysis of 501 patients with IS admitted to Sahlgrenska University Hospital from February 15, 2005, through May 31, 2009. The outcomes of interest were acute and long-term survival; the stroke severity (NIHSS) and the functional outcome, mRS, at 12 months. Results. HbA1c was a good predictor of acute (HR 1.45; CI, 1.09 to 1.93, P=0.011) and long-term mortality (HR 1.29; CI 1.03 to 1.62; P=0.029). Furthermore, HbA1c >6% was significantly correlated with acute stroke severity (OR 1.29; CI 1.01 to 1.67; P=0.042) and predicted worse functional outcome at 12 months (OR 2.68; CI 1.14 to 6.03; P=0.024). Conclusions. Our study suggests that poor glycemic control (baseline HbA1c) prior to IS is an independent risk factor for poor survival and a marker for increased stroke severity and unfavorable long-term functional outcome.